EFIKASI DIRI SEBAGAI MEDIASI DALAM HUBUNGAN LINGKUNGAN KAMPUS DAN MANAJEMEN WAKTU PADA PRESTASI MAHASISWA - Almas Farah Dinna Dewi; Moch Arfan Nur Kholidy; Ema Desia Prajitiasari (LPPM Universitas Nusa Mandiri, 2025)
Academic achievement is a crucial indicator of the success of higher education processes; therefore, understanding the factors that influence it is essential. A supportive campus environment and effective time management have been widely studied as key determinants of student academic performance, with self-efficacy often positioned as a mediating variable that links the two. At the Faculty of Economics and Business, University of Jember, field findings reveal several issues such as unstable internet access, limited discussion spaces, and underutilized academic advising services, all of which potentially affect students’ self-efficacy and academic achievement. This study aims to analyze the influence of the campus environment and time management on students’ academic performance, with self-efficacy as a mediating variable. A quantitative approach was employed using Partial Least Square Structural Equation Modeling (PLS-SEM) processed through SmartPLS 4.0. The research sample total in 270 respondents by purposive sampling consisted of active undergraduate students at the Faculty of Economics and Business, University of Jember. The results show that both the campus environment and time management have a positive and significant impact on academic achievement. Moreover, self-efficacy was found to play a significant mediating role in the relationship between campus environment and time management with academic performance. These findings highlight the importance of enhancing student self-efficacy through a well-managed learning environment and effective time management training to foster better academic outcomes.